Expression profiles of immune mediators in feline Coronavirus-infected cells and clinical samples of feline Coronavirus-positive cats - Safi, Nikoo; Haghani, Amin; Ng, Shing Wei; Selvarajah, Gayathri Thevi; Mustaffa Kamal, Farina; Omar, Abdul Rahman (BioMed Central, 2017)
Background: There are two biotypes of feline coronavirus (FCoV): the self-limiting feline enteric coronavirus (FECV) and the feline infectious peritonitis virus (FIPV), which causes feline infectious peritonitis (FIP), a fatal disease associated with cats living in multi-cat environments. This study provides an insight on the various immune mediators detected in FCoV-positive cats which may be responsible for the development of FIP. Results: In this study, using real-time PCR and multiplex bead-based immunoassay, the expression profiles of several immune mediators were examined in Crandell-Reese feline kidney (CRFK) cells infected with the feline coronavirus (FCoV) strain FIPV 79–1146 and in samples obtained from FCoV-positive cats. CRFK cells infected with FIPV 79–1146 showed an increase in the expression of interferon-related genes and pro-inflammatory cytokines such as MX1, viperin, CXCL10, CCL8, RANTES, KC, MCP1, and IL8. In addition, an increase in the expression of the above cytokines as well as GM-CSF and IFNγ was also detected in the PBMC, serum, and peritoneal effusions of FCoV-positive cats. Although the expression of MX1 and viperin genes was variable between cats, the expression of these two genes was relatively higher in cats having peritoneal effusion compared to cats without clinically obvious effusion. Higher viral load was also detected in the supernatant of peritoneal effusions compared to in the plasma of FCoV-positive cats. As expected, the secretion of IL1β, IL6 and TNFα was readily detected in the supernatant of peritoneal effusions of the FCoV-positive cats. Conclusions: This study has identified various pro-inflammatory cytokines and interferon-related genes such as MX1, viperin, CXCL10, CCL8, RANTES, KC, MCP1, IL8, GM-CSF and IFNγ in FCoV-positive cats. With the exception of MX1 and viperin, no distinct pattern of immune mediators was observed that distinguished between FCoV-positive cats with and without peritoneal effusion. Further studies based on definitive diagnosis of FIP need to be performed to confirm the clinical importance of this study.